Recent advances in boron-mediated aglycon delivery (BMAD) for the efficient synthesis of 1, 2-cis glycosides. (August 2022) - Takahashi, Daisuke; Inaba, Kazuki; Toshima, Kazunobu
Abstract: Highly stereoselective synthesis of 1, 2- cis glycosides remains a challenging task due to the lack of reliable neighboring group participation (NGP) from the 2- O -acyl functionality in the glycosyl donor. In this context, our group recently developed highly 1, 2- cis -stereoselective glycosylation methods, named boron-mediated aglycon delivery (BMAD), using organoboron reagents and 1, 2-anhydroglycosyl donors. In this mini-review article, we introduce the BMAD methods and their applications to the synthesis of biologically active natural products and complex glycosides reported since our mini-review article published in this journal in 2017. Graphical abstract: Image 1 Highlights: Regio- and β-stereoselective rhamnosylation and its application are described. Regio- and 1, 2- cis -stereoselective glycosylation of unprotected glycosides and its application are described. Diastereoselective desymmetric 1, 2- cis -glycosylation of meso -diols and its application are described.